The Arabic Root and the Peculiarities of Its Language Categorization (Structure and Inflection) - Mingazova, Nailya Gabdelkhamitovna; Al-Foadi, Raheem Ali; Subich, Vitaly Glebovich (International Journal of Criminology and Sociology, 2022)
This article discusses the peculiarities of the Arabic root, its phonemic structure, and morphological categorization. The pure appearance of the Arabic root in language categorization allows you to separate the onomatopoeic feature of inflectional structure and phonetic rules of the Arabic language by which the root is categorized. This phenomenon of meaningful consonant phonemes in the Arabic roots makes the theory of onomatopoeia practicable not just only in Arabic but also in other Semitic languages. Moreover, the first consonant of an Arabic root usually contains the word’s primary, essential meaning, and the second and third lookup. Also, in this work, it is noted that the grammar of the Arabic language has many features aimed at preserving the “purity” of the language and ensuring its continuity. It means that Arabic grammar is working as a trusted keeper of Arabic; therefore, the rules of this phenomenon are well prepared by old Arab grammarians. The Arabic root can show very useful organized peculiarities making Arabic so easy to understand and makes the Arabic words formed systematically. The article reveals “the Arabic law of language self-defense” and its basic rules, such as the principle of progressive language categorization.